Liquid biopsy for CNS lymphoma: CSF exosomes and CSF exosomal miR-15a, miR-21, miR-155, miR-210, and miR-19b are promising biomarkers for diagnosis - HATİBOĞLU M. A.; KARAÇAM B.; KHAN I.; Akdur K.; ELBASAN E. B.; Mahfooz S.; SEYİTHANOĞLU M. H.; ÇETİN G.; GUNDAG M.; ÖZTANIR M. N. (My University, 2024)
BackgroundCentral nervous system lymphoma (CNSL) is a devastating disease with a poor prognosis. Early diagnosis, monitoring of the treatment response, and outcome prediction carry the utmost importance in the management of patients with CNSL. Surgical biopsy is the gold standard for tissue diagnosis, however, this procedure has potential complications. Therefore, there is a need for a method that provides information about diagnosis and patient monitoring to avoid surgical risks. The study aimed to investigate potential diagnostic biomarkers for patients with CNSL.Methods and resultsPatients with secondary CNSL were included in this study. Serum and cerebrospinal fluid (CSF) samples were collected before treatment and after completion of the treatment. Cell-free DNA (cfDNA), exosomes, free and exosomal microRNA (miR)-15a, miR-21, miR-155, miR-210, and miR-19b in both serum and CSF were examined, and they were compared with the controls. Also, their levels before and after treatment were compared. Nine patients with the diagnosis of secondary CNSL were reviewed. cfDNA, miR-15a, and miR-155 in serum, and exosome in CSF were found to be significantly higher in CNSL patients compared to the controls. Exosomal miR-15a, miR-21, miR-155, miR-210, and miR-19b in CSF were found to be significantly higher in CNSL patients compared to controls, whereas their levels in serum were not significantly high.ConclusionsOur findings suggested that exosomes and exosomal miR-15a, miR-21, miR-155, miR-210 and miR-19b in CSF would be promising biomarkers for the diagnosis of patients with CNSL. Further studies are needed to confirm our findings.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Biyokimya Ve Moleküler Biyoloji; Moleküler Biyoloji Ve Genetik; Yaşam Bilimleri (Life); Biochemistry & Molecular Biology; Molecular Biology & Genetics; Life Sciences (Life); İlaç Keşfi; Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Biyokimya; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Drug Discovery; Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Biochemistry; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology